Immigration policy as family language policy: Mexican immigrant children and families in search of biliteracy. (June 2019) - Gallo, Sarah; Hornberger, Nancy H
Aims and objectives/purpose/research questions: In this article we draw upon the ethnography of language planning and policy (LPP) to examine the complexities of how young Latino children with a recently deported parent engage with family language policies within their routine interactions. We explore the following questions. (1) How do US elementary school-aged children engage with, resist, and refashion family language and literacy policies alongside their parents in the face of parental deportations to Mexico? (2) How do children's and parents' experiences with monoglossic ideologies of schooling in the USA and Mexico shape family LPP and migratory decisions? Design/methodology/approach: The data come from a three-year ethnography on Mexican immigrant fathers and their elementary school-aged children conducted within the context of heightened deportations. Data and analysis: We focus on the case of eight-year-old Princess following her father's deportation to examine how she articulated awareness of their counterpoint lives as she engaged in LPP alongside her mother. Findings/conclusions: Our findings reveal the unintended language education consequences of immigration policy as well as the complex ways that children discursively contribute to family LPP and migration decisions. Originality: This article uniquely highlights the complex interplay between immigration policy and LPP in the daily lives of mixed status Mexican immigrant families and the active roles that children play in shaping family language policy and migratory decisions. Significance/implications: We illustrate how children orient to monoglossic schooling ideologies as they prepare for and contest the possibilities of transnational schooling in Mexico and how limited opportunities to develop dynamic bilingualism or biliteracy in US schools shape families' decisions. We argue that educational policy and classroom practices that open up ideological and implementational spaces to dynamically develop both languages are needed to better prepare children—especially those from undocumented families within a context of unprecedented deportations—for educational success on both sides of the border.